Earth as a Hybrid Planet: The Anthropocene in an Evolutionary Astrobiological Context. (September 2017) - Frank, Adam; Kleidon, Axel; Alberti, Marina
Abstract: We develop a classification scheme for the evolutionary state of planets based on the non-equilibrium thermodynamics of their coupled systems, including the presence of a biosphere and the possibility of what we call an "agency-dominated biosphere" (i.e. an energy-intensive technological species). The premise is that Earth's entry into the "Anthropocene" represents what might be, from an astrobiological perspective, a predictable planetary transition. We explore this problem from the perspective of the solar system and exoplanet studies. Our classification discriminates planets by the forms of free energy generation driven from stellar forcing. We then explore how timescales for global evolutionary processes on Earth might be synchronized with ecological transformations driven by increases in energy harvesting and its consequences (which might have reached a turning point with global urbanization). Finally, we describe quantitatively the classification scheme based on the maintenance of chemical disequilibrium in the past and current Earth systems and on other worlds in the solar system. In this perspective, the beginning of the Anthropocene can be seen as the onset of the hybridization of the planet – a transitional stage from one class of planetary systems interaction to another. For Earth, this stage occurs as the effects of human civilization yield not just new evolutionary pressures, but new selected directions for novel planetary ecosystem functions and their capacity to generate disequilibrium and enhance planetary dissipation.